Effects of a magnetic cloud simultaneously observed on the equatorial ionosphere in midday and midnight sectors - Rastogi, R. G.; Chandra, H.; Das, A.C.; Sridharan, R.; Reinisch, B. W.; Ahmed, Khurshid (My University, 2012)
An impact of a magnetic cloud on the Earth’s magnetosphere occurred at 1636 UT on 25 June, 1998, associated with a sudden increase of the solar wind density and velocity, as well as a sudden increase of the zenithal component of the interplanetary magnetic field (IMF-Bz). Following the impact of the magnetic cloud, IMF-Bz was northward (10 nT) and remained steadily strong (about 15 nT) for the next six hours. IMF-Bz turned southward at 2330 UT on 25 June, 1998, and remained strongly southward (−15 nT) for the next four hours. During the positive phase of IMF-Bz, both the Auroral index and ring current index SYM/H remained steadily low indicating complete isolation of the Earth’s magnetosphere from the solar wind and no significant changes were observed in the equatorial ionosphere. After the southward turning, the steady southward IMF-Bz permitted solar wind energy to penetrate the magnetosphere and caused the generation of a magnetic storm associated with strong auroral electrojet activity (AE index). Strong southward IMF-Bz corresponds to the dawn-dusk interplanetary electric field (eastward on the dayside and westward on the night side). The ionograms at Jicamarca (night side) showed strong spread-F and at Thumba (dayside) showed an absence of equatorial type of sporadic-E, indicating a dusk-to-dawn electric field. Thus, the observations point to an electric field opposite in direction to that expected by the prompt penetration of the interplanetary electric field. An abnormally-large Auroral index (AE) associated with the start of the storm suggests that the cause of the equatorial electric field changes is due to the disturbance dynamo effect.
Keywords: Interplanetary magnetic field; Equatorial ionospheric irregularities; Equatorial electrojet; Counter electrojet; IMF